Ефекат садржаја ретикулоцитног хемоглобина на дијагнозу анемије са недостатком гвожђа: студија метаанализе - KILIÇ, MERVE (Journal of Medical Biochemistry, 2021)
Background: Iron deficiency anemia (IDA) is the most common type of anemia worldwide and has many negative effects on life quality. This meta-analysis study aims to show reticulocyte hemoglobin concent (CHr) is more effective than routinely used parameters in the diagnosis of IDA.Methods: Comprehensive and systematic research was done using international databases including PubMed, Web of Science, Cochrane Library, Science Direct, and Google Scholar, which contain all articles published on IDA until December 29, 2020. Seventeen articles were included in the meta-analysis.Results: The analyses found the Cohend’s d effect size (Standardized Mean Difference) values of the parameters. Accordingly, CHr is 2.84(95% CI 2.36 to 3.31), mean corpus volume (MCV) is 2.46 (95% CI 1.97 to 2.95), ferritin is 2.37(95% CI 1.63 to 3.11), and transferrin saturation (TSAT) is 3.76(95% CI 2.14 to 5.38). To diagnose IDA, the sensitivity value of the CHr concentration was found as 83.5% (95% CI 76.1 to 89.8), specificity value to be 91.8% (95% CI 85.5 to 96.4), and mean cut-off value as 28.2 pg.Conclusion: This study is the first meta-analysis to evaluate the efficiency of CHr in the diagnosis of IDA. The results of our study reveal that; CHr level is a better biomarker than MCV and ferritin used in the determination of IDA, and its selectivity was found to be lower than that of TSAT. The groups in the study are heterogeneous but contain bias. Meta-analyses of studies with less heterogeneity of CHr are needed.